The human CIB1-EVER1-EVER2 complex governs keratinocyte-intrinsic immunity to beta-papillomaviruses (2018)
ABSTRACT: Patients with epidermodysplasia verruciformis (EV) and biallelic null mutations of TMC6 (encoding EVER1) or TMC8 (EVER2) are selectively prone to disseminated skin lesions due to keratinocyte-tropic human β-papillomaviruses (β-HPVs), which lack E5 and E8. We describe EV patients homozygous for null mutations of the CIB1 gene encoding calcium- and integrin-binding protein-1 (CIB1). CIB1 is strongly expressed in the skin and cultured keratinocytes of controls but not in those of patients. CIB1 forms a complex with EVER1 and EVER2, and CIB1 proteins are not expressed in EVER1- or EVER2-deficient cells. The known functions of EVER1 and EVER2 in human keratinocytes are not dependent on CIB1, and CIB1 deficiency does not impair keratinocyte adhesion or migration. In keratinocytes, the CIB1 protein interacts with the HPV E5 and E8 proteins encoded by α-HPV16 and γ-HPV4, respectively, suggesting that this protein acts as a restriction factor against HPVs. Collectively, these findings suggest that the disruption of CIB1-EVER1-EVER2-dependent keratinocyte-intrinsic immunity underlies the selective susceptibility to β-HPVs of EV patients.